SHAYKHZODA POETICALLY SHOOK MODERN PEN - Boykhurozov Diyorbek Sherzod ugli (TADQIQOTLAR, 2025)
Annotation: in the poetic work of the Sheikhzoda, he shook pen, mainly on modern topics, and in his dramaturgy, a thoughtful look at the historical past and gave new artistic life to the siymos and events that help to illuminate the modern problems in  it.  One  of  the  outstanding  manifestations  of  Uzbek  literature,  the  famous  poet, zabardast playwright, literary scholar and translator Maqsud Shaykhzoda stood out from all of us not only in the sense of reason, but also in the sense of siymo. The idle question of the autonomous mouth did not seem to melt into it.